Whitehead's principle. (6th April 2020) - Blumson, Ben; Singh, Manikaran
Abstract: According to Whitehead's rectified principle, two individuals are connected just in case there is something self‐connected which overlaps both of them, and every part of which overlaps one of them. Roberto Casati and Achille Varzi have offered a counterexample to the principle, consisting of an individual which has no self‐connected parts. But since atoms are self‐connected, Casati and Varzi's counterexample presupposes the possibility of gunk or, in other words, things which have no atoms as parts. So one may still wonder whether Whitehead's rectified principle follows from the assumption of atomism. This paper presents an atomic countermodel to show the answer is no.